Desenvolvimento de uma formulação lipossomal de uso tópico contendo o peptídeo sintético PnPP-19 para o tratamento da disfunção erétil & análise de patentes em biotecnologia, na área de fármacos e medicamentos, que exploram venenos e toxinas provenientes da fauna brasileira - Flávia De Marco Almeida (2015)
In Part I, this work describes the development of a liposomal formulation containing PnPP-19, derived from the toxin PnTx2-6 from Phoneutria nigriventer spider, for the topical treatment of erectile dysfunction (ED). PnPP-19 is a 19-amino-acid synthetic peptide previously described as a novel bioactive compound for the treatment of erectile dysfunction. The aim of this work was to evaluate the physicochemical properties of cationic transfersomes containing PnPP-19 and the skin permeation of PnPP-19, whether free or encapsulated. Three different liposomal preparation methods were evaluated. Cationic transfersomes contained egg phosphatidyl choline, stearylamine and Tween 20. Lipid concentration varied from 20mM to 40mM. We evaluated the entrapment efficiency, mean diameter, zeta potential and stability at 4oC of the formulations. The skin permeation assays were performed with abdominal human skin using Franz diffusion cell with 3 cm2 diffusion area at 32oC and a fluorescent derivative of the peptide, containing 5-TAMRA, bound to PnPP-19 C-terminal region, where an extra lysine was inserted. Our results showed variable entrapment efficiencies, from 6% to 30%, depending on the preparation method and the lipid concentration used, and reversed phase evaporation at 40 mM lipid concentration led to the best entrapment efficiency (30,2 + 4,5 %). Free PnPP-19 was able to permeate skin at a rate of 10.8 ng/cm2/h. However, PnPP-19 was specifically hydrolyzed by skin proteases, generating a fragment of 15 amino acid residues. Encapsulated PnPP-19 permeated skin at a rate of 12.6 ng/cm2/h. The encapsulation in cationic transfersomes protected the peptide from degradation, favoring its topical administration. The use of drugs developed from the exploitation of the Brazilian biodiversity, as in the present work, is in a stage of regulamentation in Brazil. The provisional measure MP 2.186-16, into force since August 2001, revogated by the law 13.123, on May 20, 2015, was extensively questioned by Brazilian researchers, and has affected scientific and technological production. In this context, Part II involves a search at patent banks for inventions developed in Brazil and abroad, filed between 2000 and 2011, that describe drugs or medicines developed after venoms, toxins or their derivatives from the Brazilian fauna. Our results show that only 8 Brazilian genera are involved in patent applications. The inventions mostly involve anticancer compositions, antimicrobials, vaccines and hypotensives. Brazilian inventors hold 49% of the patent applications, and the other applications were filed by American and European inventors. Therefore, there is still a great arsenal of venom molecules from the rich Brazilian fauna to be explored for the development of new bioactive compounds. Brazilian laws that rule the investigation and commercial exploitation of products comprising the use of Brazilian genetic resources are also discussed herein.